Opening Statement: Rainer Geiger - CADE, Conselho Administrativo De Defesa Econômica (Revista do IBRAC, 2025)
I am pleased to represent the OECD at this conference which will be a landmark for competition policy in Brazil, Latin America and worldwide. This is an important event, bringing together policy makers, public officials, private sector representatives from 21 countries for a wide ranging discussion on crucial issues of competition policy and economic reform